Raising Health Awareness in Rural Communities: A Randomized Experiment in Bangladesh and India - Siddique, Abu; Rahman, Tabassum; Pakrashi, Debayan; Islam, Asad; Ahmed, Firoz (The Review of Economics and Statistics, 2024)
Abstract Delivering validated information to rural areas is a major challenge in low-income countries. In this paper, we study information provision to rural communities in the context of a global outbreak of an infectious disease—COVID-19. Two weeks after the initial lockdown in March 2020, we conducted a randomized experiment in rural Bangladesh and India to disseminate health information over the phone. We find that relative to information provided via SMS, phone calls can significantly improve people’s awareness and compliance with health guidelines. We also find compliance to be substantially higher among women, which also persists after three months of the campaign.